Systemic immune-inflammation index and systemic inflammation response index levels are associated with coronary heart disease prevalence in the asthmatic population: a cross-sectional analysis of the NHANES 2011–2018 - Wu, Xian; Zhang, Haiyang; Liu, Hanmin (Frontiers in Public Health, 2025)
BackgroundEarlier studies have indicated a positive correlation systemic immune-inflammatory index (SII) and systemic inflammatory response index (SIRI) levels and the development of coronary heart disease (CHD). However, the correlation between SII, SIRI levels and the incidence of CHD in patients with asthma has not been described. The purpose of the study was to research the potential correlation between the levels of SII, SIRI and the incidence of CHD in patients with asthma.MethodsWe conducted a retrospective cross-sectional analysis in which data of individuals from the National Health and Nutrition Examination Survey (NHANES) between 2011 and 2018. This study included 39,156 adults. Weighted multivariable regression analysis and subgroup analyses were used to assess the independent and combined associations between CHD prevalence and SII, SIRI levels of asthmatic population.ResultsTotally, 2,321 adults were included in our analysis, with 116 participants experiencing CHD and the remaining 2,205 participants being free of CHD. SII levels did not significantly correlate with any of the participants' baseline characteristics, nor did SIRI levels (r < 0.1). Higher levels of SII were related to increased incidence of CHD, with an OR of 1.462 (95% CI, 1.031–1.893) (p < 0.001). Similarly, SIRI levels had similar results, with OR of 1.268 (95% CI, 1.095–1.441) (p < 0.05). Positive correlations between SII, SIRI levels and the incidence of CHD were observed (p < 0.05). Curve fitting further illustrated a positive correlation between SII, SIRI and the incidence of CHD in participants with asthma. Threshold effect analysis showed that higher levels of SII and SIRI were associated with a higher incidence of CHD, especially when SII and SIRI levels exceeded the thresholds of 411.238 and 1.812. Stratified analyses confirmed that the associations between higher SII and SIRI and increased CHD incidence in most subgroups remained consistent.ConclusionsThe incidence of CHD in asthmatic individuals was positively correlated with elevated SII and SIRI levels among US adults. SII and SIRI serve as recently emerged inflammatory markers for assessing CHD prevalence in the asthmatic population. However, in order to confirm these findings, more rigorous large-scale prospective studies are needed.